A method for measuring the uncertainty of the assessed magnitude of community outrage - Smolarkiewicz, Marcin (Metoda pomiaru niepewności szacowanej wielkości oburzenia społeczności, 2025)
A quantitative, or even semi-quantitative, measurement of community outrage – introduced by Sandman as a component of socially driven risk – is difficult to perform. Nevertheless, by applying the unique methodology proposed by Wolanin, Kępka, and Telak, such measurement becomes feasible through the categorisation of emotional states and the use of social research based on assessing the sense of safety. This article discusses an original methodology that enables not only the estimation of the magnitude of community outrage but also the assessment of the uncertainty associated with its measurement. Knowledge of this uncertainty has a significant impact on risk-informed decision-making.
Zeszyty Naukowe Collegium Witelona, nr 54(1)/2025, s. 67-77
Keywords: risk; Shannon entropy; assessment of risk uncertainty; community outrage